From Pasture-Lands to Wilderness - Sanja Đurin (Svetovi)
The article deals with the Velebit mountain range and how it has become established within wilderness discourse. For the sake of tourism, it is today presented as “wild”, as a place of adventure and wilderness; however, Velebit mountain was for centuries a place where herders and their families coexisted with the Velebit landscape. This article discusses the dominant wilderness narrative of Velebit mountain range in the context of adventure tourism. The discourse on Velebit has changed in the past ten to fifteen years, ever since tourism in Croatia has been taken in a new direction with the goal of becoming a destination for active holidays. Based on ethnographic and archival work, online content, blogs and travel literature analysis, the paper describes this switch in the cultural meaning of Velebit.